Abundance, dry matter production and nutritional value of forage shrub legumes from the dry tropics - Guerrero-Rodríguez, Juan de Dios; Bustamante-González, Angel; Aceves-Ruiz, Ernesto; Vargas-López, Samuel; Calderón-Sánchez, Francisco; Pérez-Ramírez, Efrain; Olvera-Hernández, José Isabel (Ecosistemas y Recursos Agropecuarios, 2021)
The dry forest has a wide diversity of species of tree legumes useful as feed for ruminants, of which little is known. Therefore, the objective was to evaluate seven species that goats prefer the most, to determine their frequency in the pasture, production of dry leaf matter and nutritional quality. The relative frequency in the pasture was quantified using 20x20 m quadrants. With measurements of the plant structure, in each species regression models were generated for the prediction of the dry matter production of leaf and, the crude protein, fibers and in vitro digestibility were quantified. The relative frequency varied considerably between species (P < 0.0001); Acacia cymbispina was more abundant. In the dry matter production of the leaf, the characteristics of the main stem and the tree's crown had a greater contribution to its estimation. The species differed (P < 0.0001) in crude protein concentration, averaging between 13.2 to 20.6 % and with a tendency to decrease in Mimosa polyantha, Senna wislizeni and Lysiloma tergemina as the growth cycle progressed. Although the species were different in the fiber concentration (P < 0.0001), in acid detergent fiber greater differences were observed, varying in a range from 14.8 to 28.7 %, an aspect negatively correlated with in vitro digestibility. The most abundant species was A. cymbispina. The species with the highest concentration of crude protein was Acacia farnesiana, the most digestible was S. wislizeni, and the one with the lowest protein concentration and digestibility was Acacia milibekii.